SKIL Promotes Pancreatic Cancer Metastasis by Inhibiting TSPYL2 to Activate the TGF‐β Pathway - Chenxi Wang; Weiwei Song; Yixuan Zhang; Hongming Deng; Zixiang Zhou; Jing Zhu; Xiaobing Wang (Cancer Innovation)
ABSTRACT Background Pancreatic adenocarcinoma (PAAD) represents a highly fatal form of cancer. The 5‐year survival rate for patients with this disease is only around 10%. A significant hurdle in its management is the absence of characteristic early‐stage symptoms. As a result, a large majority of pancreatic cancer patients are diagnosed when the disease has reached an advanced stage or has metastasized. Consequently, taking measures to suppress the occurrence of metastasis in pancreatic cancer can bring about a substantial improvement in patients' survival rates and overall prognosis. SKIL, known to promote cancer progression, is implicated in cell proliferation, epithelial–mesenchymal transition (EMT), and metastasis, but its specific function in pancreatic cancer remains unclear. Methods We investigated the effects of SKIL on the proliferation, apoptosis, and metastasis of pancreatic cancer cells. Through ChIP‐seq, we identified the SKIL downstream target gene and further explored the mechanism by which SKIL regulates the metastasis of pancreatic cancer cells through functional experiments and Western blot. Results A high level of SKIL expression is associated with an unfavorable prognosis in PAAD; it promotes cell migration and EMT. Through ChIP‐seq analysis, we identified that SKIL inhibits TSPYL2, a nuclear protein regulating the TGF‐β pathway by binding to the TGFB1 promoter. Further studies carried out by us confirmed that SKIL modulates the TGF‐β pathway via TSPYL2, facilitating EMT and metastasis in pancreatic cancer cells, independent of Smad4. Conclusions These findings reveal a novel regulatory mechanism involving SKIL, TSPYL2, and the TGF‐β pathway, offering new therapeutic targets for PAAD.